Rola retoryki w oracjach pogrzebowych. Uwagi na marginesie mów funeralnych i wspomnień pośmiertnych poświęconych Alojzemu Felińskiemu - Patro-Kucab, Magdalena (Słowo. Studia językoznawcze, 2015)
Post mortem speeches delivered to commemorate Alojzy Feliński have not been edited scientifically nor in any other form so far. In 2004 Andrzej Krzysztof Guzek reported the need to devote a separate chapter to the Krzemieniecki and Warsaw reactions to the death of the secondary school headmaster. The author of Barbara Radziwiłłówna was bid farewell by: Alojzy Osiński, Jan Sowiński, Jan Tarnowski, Wincenty Turski, Michał Wyszkowski and Tymon Zaborowski, among others. The subject of my dissertation are the three speeches created after the death of Feliński, published so far only in the 19 th century as spontaneous occasional printings or in contemporary magazines (“Pszczoła Polska” 1820; “Roczniki Towarzystwa Królewskiego Warszawskiego Przyjaciół Nauk” 1821). In exemplification, using the differentiation by Julius Caesar Scaliger, I reach for the example of epicedium – an oration given over the unburied body and epitaph – a work delivered over the grave or on subsequent death anniversaries. The orations presented by me do not demonstrate a stylistic proficiency of their authors but provide real science, they are the praise of beauty and goodness. They constitute a grateful contamination of genus demonstrativum, the theory of funeral speech according to Menander and recommendations formulated by Filip Neriusz Golański, Franciszek Karpiński or Józef Korzeniowski. The structural outline of both orations utilizes a classic version that includes a three-part scheme, which ordered the story of a figure to include three periods of their life: before birth, while alive and after death. In the first part, the authors refer to famous ancestors of the deceased (Józef Czech and Tadeusz Czacki). In the description of life, the laudators include (in varying degrees) his spiritual virtues and praise merits (love for the homeland, excellent holding of the office, goodness, politeness, joy, dramatist and poet talent). They talk about the way he died, and recall how he would be remembered by the descendants. However, when portraying the virtues of the deceased the orators do not exaggerate Feliński’s virtues, and for amplification they use well-known rhetoric tools but they do not create fiction. The orators have adapted their funeral speeches to rhetoric rules and new currents that were valid in the rhetoric. The authors also took care of the artistic part of their orations through relevant selection of rhetoric figures that were used not for pleasure purposes (delectare) but rather for emotional ones (movere) and to remind of transitoriness of human life (docere).